Guidance and Counseling based on Sûrat al-Fãtihah - Kurnanto, Muhammad Edi (Jurnal Pendidikan Islam, 2016)
Among the forms of guidance and counseling development there is the emergence of Islamic variety based models of guidance and counseling. One of them is model of al-Fãtihah-Based Guidance and Counseling (FBGC). The model was developed from the belief that science in the study of the Qur'an, especially al-Fãtihah has its own place, both in the study of its name and its content. Because it was developed from sũrat al-Fãtihah, all the elements of the service, starting from the philosophical basis, guidance objective, material, procedures, counselors’ competencies and evaluation as well as indicators of the success of the service all are extracted from the contextualization of sũrat al-Fãtihah. This paper was developed from a study of literatures. After doing the library study, the writer concluded that the FBGC can be used as complementary service in the implementation of guidance and counseling at Islamic school to support the embodiment of the golden generation after one hundred years of Indonesian independence in 2045.